Ergonomic Evaluation of Mechanical Workshop Activities to Reduce Musculoskeletal Disorders - Saifun Hakim; Heru Prastawa; Novie Susanto (Universitas PGRI Semarang, 2023)
There are many brands of two-wheeled vehicles, one of which is Honda. Entering 1982 to 1984 Honda released the CB 100 and CB 125 with a more attractive appearance. In the type of CB in 1978 to Tiger Revo 2012 has a change in shape that shows the development of innovation. To fulfil the demands of work in the workshop, mechanics experience various types of movements such as moving, bending, turning, holding machines and installing manually without the help of ergonomic aids. This study was conducted on 5 workshop mechanics located in 33 districts/cities in Central Java province. The research results from 5 mechanics resulted in a high risk level using the NERPA, WERA and KIM methods. Then the improvement proposal is made with the design of a tool design in the form of a mechanical work table so that it can reduce the occurrence of Musculoskeletal Disorders. in calculation with tools to disassembling the machine obtained results in the NERPA method of 4 which means the activity has a medium risk. In the WERA method assessment, the final risk value is 33 with a medium risk value. The third calculation using KIM obtained a final risk value of 40 at level 2, meaning that the intensity increased slightly. The calculation of raising the machine obtained a NERPA value of 4 with a medium risk. The WERA method obtained a value of 38 with medium risk. The third calculation using KIM obtained a value of 35 with a level 2 value.